2017
DOI: 10.15252/embr.201744632
|View full text |Cite
|
Sign up to set email alerts
|

WDR11‐mediated Hedgehog signalling defects underlie a new ciliopathy related to Kallmann syndrome

Abstract: WDR11 has been implicated in congenital hypogonadotropic hypogonadism (CHH) and Kallmann syndrome (KS), human developmental genetic disorders defined by delayed puberty and infertility. However, WDR11's role in development is poorly understood. Here, we report that WDR11 modulates the Hedgehog (Hh) signalling pathway and is essential for ciliogenesis. Disruption of WDR11 expression in mouse and zebrafish results in phenotypic characteristics associated with defective Hh signalling, accompanied by dysgenesis of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 68 publications
(89 reference statements)
5
65
0
1
Order By: Relevance
“…Intriguingly, mutations of WDR11 have been found in patients with congenital hypogonadotropic hypogonadism (CHH) and Kallmann syndrome (KS), developmental disorders characterized by delayed puberty and infertility . WDR11 is essential for normal ciliogenesis, by being involved in the Hedgehog (Hh) signaling pathway (Kim et al, 2018). However, it is unclear whether TBC1D23 is also involved in these processes.…”
Section: Wdr11mentioning
confidence: 99%
“…Intriguingly, mutations of WDR11 have been found in patients with congenital hypogonadotropic hypogonadism (CHH) and Kallmann syndrome (KS), developmental disorders characterized by delayed puberty and infertility . WDR11 is essential for normal ciliogenesis, by being involved in the Hedgehog (Hh) signaling pathway (Kim et al, 2018). However, it is unclear whether TBC1D23 is also involved in these processes.…”
Section: Wdr11mentioning
confidence: 99%
“…WDR11 belongs to a family of proteins with the evolutionarily conserved WD40-repeat (WDR) domains, forming βpropeller structures known to mediate protein-protein interactions (7;11). Our previous studies of a Wdr11 knockout (KO) mouse model have indicated a critical role for WDR11 in development (12). Wdr11 is required for normal ciliogenesis as loss of Wdr11 resulted in short and infrequent primary cilia.…”
Section: Introductionmentioning
confidence: 99%
“…Wdr11 is required for normal ciliogenesis as loss of Wdr11 resulted in short and infrequent primary cilia. Since multiple developmental signalling pathways functionally rely on primary cilia, the majority of Wdr11 KO embryos die in utero at midgestation (after E12.5) with severe developmental defects (12). Those rare individual mice that survived through adulthood display features overlapping with KS/CHH such as delayed puberty and infertility, accompanied by reduced levels of GnRH and gonadotrophins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMDD independent stand-alone studies researching genetic regulation of mouse development include the analysis of: normal and abnormal cardiovascular development [49][50][51][52][53][54][55][56][57][58][59][60][61]; the development of the limbs, cloaca and pancreas [42,[62][63][64]; ciliopathies [65]; and the characterisation of cardiac defects in Down syndrome mouse models [66,67]. Despite its value for analysing such processes in embryos between embryonic day E8.5 and E14.5, when organogenesis is already finished, HREM also proved its value for analysing developmental processes in very early embryos immediately after implantation [68].…”
Section: Mouse Embryosmentioning
confidence: 99%